Putting grant/d terms to work: from promise to practice in inter- and transdisciplinary research projects - Stina Powell; Sofie Joosse (Discover Sustainability, 2024)
Abstract Sustainability research is increasingly based on inter- and transdisciplinary research approaches (IDR and TDR). In this article, we examine how grant terms (used in grant proposals for IDR and TDR projects) are put into practice. We analyzed three research projects to study how TDR and IDR are performed and why, and what we can learn for sustainability research. From a feminist perspective and using a conceptual framework including empty signifiers, comfort words and non-performativity we explore the difficulty of performing the terms, and the risk that they remain merely grand terms, promising and useful for proposals, but not guiding everyday research practice. Based on the analysis, we present seven patterns that complicate performing the terms. We suggest that these patterns can be helpful for other researchers developing their TDR and IDR research practice.